Mismatches in youth sports talent development - Carvalho, H. M.; Gonçalves, C. E. (Frontiers in Sports and Active Living, 2023)
The growing pressure to identify and nurture talented athletes for adult competitions has led sports organizations to invest significant efforts in identifying markers of talent at increasingly younger ages (1, 2). Initially, coaches were responsible for this task, but over time, it has shifted towards sport scientists (3, 4). However, in most cases, the final decision regarding the evaluation and development of young prospects still rests with the coaches (5).